Analisis Produk Layanan Emas Bank Syariah Indonesia Berdasarkan POJK Nomor 17 Tahun 2024 - Mayang Khairunnisa Syabrina; Rahmatul Fadhil (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The purpose of this study is to analyze the implementation of gold service products at BSI KCP Jakarta Gedung Pusat Kehutanan and to examine their compliance with the aforementioned OJK Regulation Number 17 of 2024 Concerning the Organization of Bullion Business Activities, while still considering Sharia principles. This study employs a qualitative research method with a normative approach through a case study. Primary data were obtained from interviews, while secondary data were sourced from the official website of Bank Syariah Indonesia and the BYOND BSI application. The results indicate that first, the gold service products offered by BSI KCP Jakarta Gedung Pusat Kehutanan include BSI Gold, BSI Cicil Emas (Gold Installment), BSI Gadai Emas (Gold Pawn), BSI E-Mas, and Safe Deposit Box. Second, the implementation of these services generally complies with OJK Regulation No. 17 of 2024, although two provisions have not yet been implemented, namely the Gold Savings service and the minimum gold weight requirement of 500 grams per transaction.